2010
DOI: 10.1080/19315261003669858
|View full text |Cite
|
Sign up to set email alerts
|

Combining Ability for Yield and Fruit Quality inLuffa

Abstract: The mating design (Line and Tester) has been extensively used to estimate general combining ability (GCA) and specific combining ability (SCA) variance and their effects. This design is also used to understand the nature of gene action involved in expression of economically important traits. Diallel analysis and combining ability in Luffa acutangula (L.) Roxb have not been extensively reported. Combining ability of 13 traits was examined in 45 Luffa hybrids derived from a 10 × 10 diallel mating design (excludi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
7
2
0
Order By: Relevance
“…Flesh in thickness the cross L 3 xT 4 (0.30) showed significant positive sca effect. These results are in agreement with Tyagi et al, (2010).…”
Section: Resultssupporting
confidence: 93%
“…Flesh in thickness the cross L 3 xT 4 (0.30) showed significant positive sca effect. These results are in agreement with Tyagi et al, (2010).…”
Section: Resultssupporting
confidence: 93%
“…These crosses can be directly utilized for improvement of these char acter s thr ough the exploitation of heterosis or can be exploited for the development of better tr ansgressive segregants, since the parents Pusa Nutan, GARG-1, Jaipur Long and CO-1 involved in these crosses also exhibited high GCA. Similar r esults wer e r epor ted by Narasannavar et al (2014b), Niyaria and Bhalala (2001), Mole et al (2001), Sarkar et al (2015), Lodam et al (2009) and Tyagi et al (2010).…”
Section: Resultssupporting
confidence: 85%
“…and Jaipuri Long x Swarna Manjari (63.82%) in E 4 exhibited highest heterobeltiosis and some other crosses like AHRG-1 x Swarna Uphar in E 2 , Swarna Uphar x Jaipuri Long in E 2 and E 3 , Jaipuri Long x Swarna Manjari, Swarna Uphar x Arka Sujath, Pusa Nasdar x Jaipuri Long, Pusa Nasdar x Swarna Manjari in E 4 exhibited significant positive heterobeltiosis for total fruit yield per vine. These results are conformity with the studies of Tyagi et al, (2010), Anand (2012), Reddy et al, (2013), Karmakar et al, (2014), Koppad et al, (2015) and Poshiya et al, (2015) who have reported a positive and significant standard heterosis for fruit length and total fruit yield found in ridge gourd.…”
Section: Resultssupporting
confidence: 81%